Identification of Conserved Amino Acid Substitutions During Serial Infection of Pregnant Cattle and Sheep With Bovine Viral Diarrhea Virus - Kuca, Thibaud; Passler, Thomas; Newcomer, Benjamin W.; Neill, John D.; Galik, Patricia K.; Riddell, Kay P.; Zhang, Yijing; Walz, Paul H. (Frontiers in Microbiology, 2018)
Bovine viral diarrhea virus (BVDV) is an economically important pathogen of cattle that can also infect a wide range of domestic and wild species including sheep, goats, deer, camelids, and pigs. BVDV isolates are genetically highly diverse and previous work demonstrated that many substitutions were introduced in the viral genome during acute infections in cattle. In contrast, only limited information exists regarding changes occurring during BVDV infections in species other than cattle. The purpose of this study was to determine the changes introduced in the open reading frame (ORF) of the BVDV genome during serial infection of pregnant cattle and sheep with an isolate of bovine origin. Serial experimental inoculations were performed in six pregnant heifers and six pregnant ewes using BVDV-1b isolate AU526 in the first heifer and ewe, and serum from the preceding acutely infected dam thereafter. Complete ORF sequences were determined for 23 BVDV-1b isolates including AU526, one isolate from each pregnant dam, and one isolate from each BVDV-positive offspring born to these dams. Sequence comparison revealed that greater numbers of substitutions occurred during serial infection of pregnant sheep than of pregnant cattle. Furthermore, multiple host-specific amino acid changes were gradually introduced and conserved. These changes were more abundant in ovine isolates and occurred primarily in the E2 coding region. These results suggest that BVDV infections in heterologous species may serve as a significant source of viral genetic diversity and may be associated with adaptive changes.